Calming Ethnic Conflicts: The Role of the form of Government - Zaznaev, Oleg; Sidorov, Viktor (International Journal of Criminology and Sociology, 2022)
This article discusses the causation between forms of government, on the one hand, and ethnic conflicts on the other. This topic has received little attention in political science. The article gives a critical review of academic discussions on the relationship between ethnic conflicts and forms of government. How to calm ethnic conflict through the combination of institutions that represent ethnic groups’ interests and provide peaceful ethnic dialogue? Which institutional design prevents ethnic conflicts? Prevention and resolution of ethnic conflicts are the functions of political institutions in a multi-ethnic society. Calming ethnic conflict could come from both an institutional and a non-institutional manner. The form of government is the institutional mechanism for managing ethnic conflicts, along with the decentralization of power and the electoral system. Empirical and theoretical observations show that ethnic conflict is more likely to happen in parliamentary systems than presidential ones, but other political institutional arrangements are important too. The authors present arguments for supporting this conclusion.